Tinjauan Holistik Tari Goyang Ngamprok di Sanggar Ayodya Pala Kotamadya Depok Jawa Barat - Nurul Syabani; Syahrial Syahrial; Maryono Maryono; R.M. Pramutomo (Universitas Negeri Medan, 2026)
This research aims to describe and analyze the meaning of the Goyang Ngamprok danceat the Ayodya Pala Studio in Depok Municipality, West Java. This research uses a qualitative research method with a Holistic Critical Approach that places three factors, namely genetic factors, objective factors, and affective factors, as a single entity as the source of meaning. The meaning of dance can be revealed by examining three issues: (1) How are the genetic factors of the Goyang Ngamprok dance at the Ayodya Pala Studio in Depok Municipality, West Java, (2) How are the objective factors of the Goyang Ngamprok dance at the Ayodya Pala Studio in Depok West Java, (3) How the Affective Factors of the Goyang Ngamprok Dance at the Ayodya Pala Studio in Depok Municipality, West Java. The data collection methods used were observation, interviews, and literature review. The research results show that the Ngamprok Dance tells the story of teenage friendships among a group of young people who experience misunderstandings but eventually quickly reconcile and become close again. The music of Goyang Ngamprok dance utilizes Betawi traditional music, fan properties, and corrective makeup.